(untitled) (Revista de História da UEG (REVHIST), 2020)
Abstract: This article aims to elucidate the historical context of the birth of scholastic thought, from patristic until its emergence, in the late 10th and early 11th centuries. This survey can help explaining how reason, a tool used by scholasticism, becomes prominent to prove and substantiate theological truths. It is also relevant in order to understand the historical moment prior to the time Anselmo lived, and how this context, possibly, influenced the thinking of the Benedictine in his work Proslogion, monk in the formation of his Ontological concept. Keywords: Scholastic. Anselm. Ontological Argument.